A pilot study to assess the learning environment and use of reliability enhancing work practices in VHA cardiac catheterization laboratories - Heather M. Gilmartin; Edward Hess; Candice Mueller; Mary E. Plomondon; Stephen W. Waldo; Catherine Battaglia (Wiley, 2021)
Abstract Introduction A learning health system (LHS) harnesses data and analytics to learn from clinical encounters to implement the best care with high reliability. The 81 Veterans Health Administration (VHA) cardiac catheterization laboratories (cath lab) are a model LHS. The quality and safety of coronary procedures are monitored and reported by the Clinical Assessment, Reporting and Tracking (CART) Program, which has identified variation in care across cath labs. This variation may be due to underappreciated aspects of LHSs, the learning environment and reliability enhancing work practices (REWPs). Learning environments are the educational approaches, context, and settings in which learning occurs. REWPs are the organizational practices found in high reliability organizations. High learning environments and use of REWPs are associated with improved outcomes. This study assessed the learning environments and use of REWPs in VHA cath labs to examine factors supportive of learning and high reliability. Methods In 2018, the learning organization survey‐27 and the REWP survey were administered to 732 cath lab staff. Factor analysis and linear models were computed. Unit‐level analyses and site ranking (high, low) were conducted on cath labs with >40% response rate using Bayesian methods. Results Surveys from 40% of cath lab staff (n = 294) at 84% of cath labs (n = 68) were included. Learning environment and REWP strengths across cath labs include the presence of training programs, openness to new ideas, and respectful interaction. Learning environment and REWP gaps include lack of structured knowledge transfer (eg, checklists) and low use of forums for improvement. Survey dimensions matched established factor structures and demonstrated high reliability (Cronbach's alpha >.76). Unit‐level analyses were conducted for 29 cath labs. One ranked as high and four as low learning environments. Conclusions This work demonstrates an approach to assess local learning environments and use of REWPs, providing insights for systems working to become a LHS.